We need to talk about error: causes and types of error in veterinary practice. (31st October 2015) - Oxtoby, C.; Ferguson, E.; White, K.; Mossop, L.
Abstract : Patient safety research in human medicine has identified the causes and common types of medical error and subsequently informed the development of interventions which mitigate harm, such as the WHO's safe surgery checklist. There is no such evidence available to the veterinary profession. This study therefore aims to identify the causes and types of errors in veterinary practice, and presents an evidence based system for their classification. Causes of error were identified from retrospective record review of 678 claims to the profession's leading indemnity insurer and nine focus groups (average N per group=8) with vets, nurses and support staff were performed using critical incident technique. Reason's (2000) Swiss cheese model of error was used to inform the interpretation of the data. Types of error were extracted from 2978 claims records reported between the years 2009 and 2013. The major classes of error causation were identified with mistakes involving surgery the most common type of error. The results were triangulated with findings from the medical literature and highlight the importance of cognitive limitations, deficiencies in non‐technical skills and a systems approach to veterinary error.